Organization of financial management aimed at reducing financial crisis in the work of individual agricultural producers and IPARD in the Republic of Serbia - Jović Vladan (Ekonomija: teorija i praksa)
This study highlights the significance of access to funding as a key mechanism through which the European Union supports the development of specific economic activities in countries aspiring to EU membership. The primary objective was to examine the behavioral patterns of individual agricultural producers in relation to fund financing through the IPARD program, particularly concerning the acquisition of new agricultural machinery. The findings reveal notable differences in the conditions for obtaining IPARD funds, especially with respect to the age of applicants. Additionally, the results indicate that the type of agricultural production also influences producers' decisions to engage in credit arrangements with the program. The practical relevance of these findings lies in emphasizing the role of producers' age in applying for loans aimed at improving the technical conditions of agricultural production, in line with the IPARD-1 measures applicable in the Republic of Serbia.